Performance art from futurism to the present. - Goldberg, R. (London : Thames and Hudson, 1979)
Anderson, Laurie ; Armitage, Karole ; Arp, Hans (Jean) ; Ball, Hugo ; Balla, Giacomo ; Bausch, Pina ; Beuys, Joseph ; Boccioni, Umberto ; Bogosian, Eric ; Breton, André ; Brown, Trisha ; Burljuk, David ; Burton, Scott ; Cage, John ; Carrà, Carlo ; Clair, René ; Colette ; Coum Transmissions ; Cunningham, Merce ; Delaunay, Sonia ; Depero, Fortunato ; Dine, Jim ; Duchamp, Marcel ; Fabre, Jan ; Fenley, Molissa ; Finlay, Karen ; Foregger, Nikolai ; Foreman, Richard ; General Idea ; Gilbert & George ; Graham, Dan ; Grosz, George ; Halprin, Ann ; Heartfield, John ; Hennings, Emmy ; Heyward, Julia ; Hirschfeld-Mack, Ludwig ; Horn, Rebecca ; Janco, Marcel ; Jarry, Alfred ; Jesurun, John ; Jonas, Joan ; Jones, Bill T. ; Kaprow, Allan ; Kiesler, Frederick ; Klein, Yves ; Kokoschka, Oskar ; Kounellis, Jannis ; Longo, Robert ; Magnuson, Ann ; Malevich, Kasimir ; Manzoni, Piero ; Marinetti, Filippo Tommaso ; Mayakovsky, Vladimir ; Meyerhold, Vsevolod ; Monk, Meredith ; Morris, Robert ; Murrin, Tom ; Nitsch, Hermann ; O'Daly, Raymond ; Oleszko, Pat ; Ontani, Luigi ; Oppenheim, Dennis ; Payne, Miranda ; Picasso, Pablo ; Piper, Adrian ; Popova, Liubov ; Prampolini, Enrico ; Preiss, Gerhard ; Rauschenberg, Robert ; Richter, Hans ; Rinke, Klaus ; Russolo, Luigi ; Satie, Erik ; Schawinsky, Xanti ; Schlemmer, Oskar ; Schmidt, Kurt ; Schneemann, Carolee ; Schwitters, Kurt ; Severini, Gino ; Taeuber-Arp, Sophie ; Trasov, Vincent ; Tzara, Tristan ; Vostell, Wolf ; Whitman, Robert ; Wilke, Hannah ; Wilson, Robert ; Woodrow, Stephen Taylor ; Zane, Arne
boek